Initial Investigation into the Energy and Operational Parameters of LED Modules - Dumbrava, Vytautas; Pagodinas, Darijus; Kupciunas, Irmantas (Elektronika ir Elektrotechnika, 2016)
The paper presents an initial investigation into the energy and operational parameters of three LED modules produced by a little-known producer. The paper considers the requirements of Standards TM-21-11 and LM-80-08 applicable in measuring lumen maintenance life, as well as the requirements for temperature in measuring illuminance. The investigation introduces the structural schemes for measuring the efficiency coefficient of the AC/DC converter of LED modules and provides the obtained measurement results. The performed measurements show that the efficiency coefficients of the AC/DC converters of the examined LED modules amount to 52 %±3.5 %. According to the experimental results obtained after measuring illuminance, the established average lumen maintenance life L70 is 2,817 hours. DOI: http://dx.doi.org/10.5755/j01.eie.22.3.13944